Childfree Marriage with Regards to Islamic Jurisprudence Principles - Rahmat Nugroho; Radifa Isnain Nafila; Kasuwi Saiban (At-turas: Jurnal Studi Keislaman)
Procreation has been considered the noblest purpose of marriage as it ensures the continuation of human existence on Earth. However, a new trend has emerged among young couples known as “childfree”, where individuals or couples consciously choose not to have children after marriage. This research aims to examine this phenomenon. What is the status of marriage with the condition of being childfree? And how valid is such a contract according to the principles of Islamic jurisprudence (Fiqh)? To achieve these objectives, the researcher employed a qualitative descriptive methodology, using literature review as the primary data collection method, focusing on relevant sources related to the topic. The findings of this study indicate that the condition of being childfree in marriage contradicts the objectives of Islamic law, which emphasize procreation and the preservation of lineage. Making a deliberate decision not to have children without any legitimate reason or physical limitations constitutes an act that exceeds the boundaries set by religious teachings. Moreover, it is considered impermissible to prohibit what Allah has made permissible, which includes having children and preserving lineage. As the condition is invalid, the parties involved in the marriage contract are not obligated to fulfill this requirement, and the marriage contract remains valid.